Spasial Data Panel Dalam Menentukan Faktor-Faktor Yang Berpengaruh Terhadap Jumlah Kasus Demam Berdarah Dengue (DBD) - Anisa Nabila; Rahmadi Yotenka (Mathematics Department of Mathematics and Natural Sciences Unisda Lamongan, 2021)
Dengue Fever (DF) is an infection caused by the dengue virus, which several types of mosquitoes can spread. Indonesia has become a dengue-endemic area since 1968 and has spread in 34 provinces with 416 districts and 98 cities. In 2015 there were 126,675 cases of dengue fever in Indonesia, an increase in 2016 to 200,830 cases; the following year, it decreased to 59,047 cases. Then the cases have fluctuated every year. This study aims to look at the factors that influence dengue cases in Indonesia, especially on the islands of Java and Bali. This is because during the last five years (2015 – 2019) the highest dengue cases in Java & Bali were in Indonesia. The method used in this research is spatial analysis of panel data with the best model of SAR (spatial autoregressive models). The results of this study are the percentage of districts/cities that implement policies for healthy areas, the percentage of poor people, and health facilities have a significant effect on the number of dengue cases in Java & Bali.